2020
DOI: 10.1007/s12098-020-03186-2
|View full text |Cite
|
Sign up to set email alerts
|

Blood Component Transfusion in a Tertiary Care Hospital

Abstract: Objectives To study the rational use of the blood components in pediatric and neonatal wards. Methods It was a retrospective study conducted by department of pediatrics of a tertiary care centre in western part of India. The patients were included from the pediatric ward, pediatric surgery ward, neonatal intensive care unit (NICU), pediatric intensive care unit (PICU) over a period of three months. All the patients below 12 y of age receiving blood components, admitted in general pediatric wards, pediatric int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
1
9
1
Order By: Relevance
“…A present audit showed 60.4% of all component transfusions to be appropriate and our results are consistent with the audit conducted in a tertiary care hospital in India, conducted by Bahadur et al(59.65%). 7 However similar study done by Mumtaz et al 10 showed a comparatively higher percentage of appropriate transfusions (72.6%). An audit done by Kapse et al 11 showed maximum demands of FFP and platelet concentrates are being done by the paediatric department as compared to other departments.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A present audit showed 60.4% of all component transfusions to be appropriate and our results are consistent with the audit conducted in a tertiary care hospital in India, conducted by Bahadur et al(59.65%). 7 However similar study done by Mumtaz et al 10 showed a comparatively higher percentage of appropriate transfusions (72.6%). An audit done by Kapse et al 11 showed maximum demands of FFP and platelet concentrates are being done by the paediatric department as compared to other departments.…”
Section: Discussionmentioning
confidence: 80%
“…Many advances have been seen in the past years to encourage safe blood transfusions as non-judicious transfusions can predispose the patients to transfusion hazards and also cause wastage of health resources. 10 Hence this audit was conducted to review transfusion practices in our setup and enhance efforts in making judicious transfusions. A present audit showed 60.4% of all component transfusions to be appropriate and our results are consistent with the audit conducted in a tertiary care hospital in India, conducted by Bahadur et al(59.65%).…”
Section: Discussionmentioning
confidence: 99%
“…2, 3 The decision to transfuse is crucial because there are various complications associated with it which include transfusion transmitted diseases, ABO incompatibility, alloimmunization, bacterial contamination, gut ischemia, transfusion related acute lung injury (TRALI) and other immunomodulation phenomena. 1,[3][4][5] Various guidelines have been devised to guide transfusion practices and to outline indications of transfusions so that complications are avoided. 2,6,7 Despite these guidelines and known complications of transfusion, there have been reports of unnecessary and inappropriate blood product transfusions i.e., transfusing blood components in absence of recommended indications.…”
Section: Introductionmentioning
confidence: 99%
“…2,6,7 Despite these guidelines and known complications of transfusion, there have been reports of unnecessary and inappropriate blood product transfusions i.e., transfusing blood components in absence of recommended indications. 1,2,4,8 To our knowledge and literature search, there has been only a single study done in Pakistan to evaluate appropriateness of blood product transfusions in critically ill children in Rawalpindi, which showed significantly high percentages of inappropriate blood component transfusions. 8 This data is important to reflect our current transfusion practices and to highlight areas of improvement, teaching and training.…”
Section: Introductionmentioning
confidence: 99%
“…In both developed and developing countries, inappropriate prescription of blood components occurs in up to 36% of cases 2 . The rational prescription of transfusion therapies is essential due to limited resources and growing demand 3 .…”
Section: Introductionmentioning
confidence: 99%